2019
DOI: 10.1111/1744-7917.12664
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and functional analyses of the interaction between the Bombyx mori inhibitor of apoptosis (IAP) and nucleopolyhedrovirus IAPs

Abstract: As an important insect immune response, apoptosis plays a critical role in the interaction between baculoviruses and insect hosts. Previous reports have identified inhibitor of apoptosis (IAP) proteins in both insects and baculoviruses, but the relationship between these proteins is still not clearly understood. Here, we found that insect IAP proteins were clustered with baculovirus IAP3, suggesting that the baculovirus iap3 gene might be derived from the Lepidoptera or Diptera. We demonstrated that Bombyx mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Both BmIAP and baculoviruses encoding IAP had an inhibitory effect on apoptosis in insects (Hamajima et al, 2016;Ikeda et al, 2011). A recent study reported that the Bmiap gene might be hijacked by BmNPV iap genes during BmNPV infection owing to the direct interaction of BmNPV IAP1 and IAP2 with BmIAP in silkworm cells (Chen et al, 2019). Cellular IAP1 is a client protein of Hsp90.…”
Section: Discussionmentioning
confidence: 99%
“…Both BmIAP and baculoviruses encoding IAP had an inhibitory effect on apoptosis in insects (Hamajima et al, 2016;Ikeda et al, 2011). A recent study reported that the Bmiap gene might be hijacked by BmNPV iap genes during BmNPV infection owing to the direct interaction of BmNPV IAP1 and IAP2 with BmIAP in silkworm cells (Chen et al, 2019). Cellular IAP1 is a client protein of Hsp90.…”
Section: Discussionmentioning
confidence: 99%
“…The progression of apoptotic signaling cascades is prevented by virus-encoded apoptosis suppressors such as viral IAPs, p35, p49, and Apsup ( 55 , 78 , 79 ). Six IAPs ( iap1-6 ) have been identified in baculoviruses that inhibit apoptosis in insects ( 78 80 ). Unlike their cellular counterparts, they lack an N-terminal instability motif ( 81 ) and stabilize cellular IAPs ( 82 ).…”
Section: Viral Immune Evasion Mechanismmentioning
confidence: 99%
“…In a model mechanism, Op-IAP3 derived from OpMNPV blocks apoptosis by interacting with an unstable auto-ubiquitinating host IAP such that cellular IAP levels and antiapoptotic activity are maintained ( 82 ). Similarly, IAP1 and IAP2 from BmNPV interact with BmIAP, and both BmIAP and viral IAPs increase BmNPV proliferation in infected silkworm cells ( 80 ). Numerous studies have shown that viral protein p35 blocks apoptosis by binding ECs ( 79 , 83 , 84 ), and p49 protein binds ICs and ECs and blocks apoptosis ( 85 , 86 ).…”
Section: Viral Immune Evasion Mechanismmentioning
confidence: 99%
“…Hence, we speculated that the pattern recognition receptor BmβGRP4 might also regulate apoptosis in response to BmNPV infection. In addition, Chen et al [31] found that the B. mori inhibitor of apoptosis (BmIAP) gene had an inhibitory effect on apoptosis in silkworm cells. The expression levels of BmPTEN and BmIAP after BmβGRP4 knockdown and overexpression were evaluated through RT-qPCR analysis using the specific primers of BmPTEN and BmIAP (Table S2).…”
Section: Expression Level Analysis Of Bmpten and Bmiapmentioning
confidence: 99%